2021
DOI: 10.3389/fcell.2021.766512
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin-3 Protects Cochlear Hair Cells Against Noise-Induced Damage via the Superoxide Dismutase 2/Reactive Oxygen Species Signaling Pathway

Abstract: Mitochondrial oxidative stress is involved in hair cell damage caused by noise-induced hearing loss (NIHL). Sirtuin-3 (SIRT3) plays an important role in hair cell survival by regulating mitochondrial function; however, the role of SIRT3 in NIHL is unknown. In this study, we used 3-TYP to inhibit SIRT3 and found that this inhibition aggravated oxidative damage in the hair cells of mice with NIHL. Moreover, 3-TYP reduced the enzymatic activity and deacetylation levels of superoxide dismutase 2 (SOD2). Subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The SIRT3-SOD2 linked pathway is critical for regulating ROS production. To maintain ROS homeostasis, SIRT3 activates SOD2 via deacetylation and converts superoxide radicals to harmless oxygen or hydrogen peroxide [ 45 ]. However, whether the SIRT3-SOD2 linked pathway or any other signal is involved in the TMAO-induced ROS production in osteoclast differentiation needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The SIRT3-SOD2 linked pathway is critical for regulating ROS production. To maintain ROS homeostasis, SIRT3 activates SOD2 via deacetylation and converts superoxide radicals to harmless oxygen or hydrogen peroxide [ 45 ]. However, whether the SIRT3-SOD2 linked pathway or any other signal is involved in the TMAO-induced ROS production in osteoclast differentiation needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, SIRT3 decreased palmitate-induced inflammation in proximal tubular cells ( Koyama et al, 2011 ). In previous study, 3-TYP, a SIRT3-selective inhibitor, has been reported to aggravate oxidative damage and reduce enzymatic activity of MnSOD2 in the hair cells of mice ( Liang et al, 2021 ). 3-TYP can not only eliminate the cardioprotective effects of melatonin ( Zhai et al, 2017 ), but also activate NF-κB and NLRP3 pathways, reducing survival rate in mice ( Lv et al, 2021 ).…”
Section: Discussionmentioning
confidence: 96%
“…The method of ABR testing has been described previously (Liang et al 2021 ; Sergeyenko et al 2013 ). Briefly, it was conducted in sound-proof room using BioSigRZ software (Tucker-Davis Technologies, USA).…”
Section: Methodsmentioning
confidence: 99%